Using FlipGrid to Improve Memory Ability in Learning Foreign Languages - Chandra, Mei Rianto (Lingua Cultura, 2022)
The research showed that online media was expected to provide a more straightforward understanding to students in learning Mandarin, one of which was FlipGrid online learning media. Learning Mandarin was quite challenging if it was only done by using textbooks. This could be shown by the lack of students’ memory of the vocabulary they had just learned. The data were analyzed with a quantitative approach involving 110 students aged 13 to 14. The data was collected of students’ vocabulary study after two months of using three test questions: filling in the blanks, guessing the meaning, and completing sentences. Thus, it can be concluded that understanding the vocabulary learned on the FlipGrid platform media can also be an additional vocabulary for students in developing speaking skills. The results reveal that the teacher’s participation in monitoring the completion of students’ assignments also plays a vital role in developing students’ speaking skills, which means that the frequency of using FlipGrid directly impacts students’ memory skills. However, when faced with critical thinking test questions, students themselves must be able to think out of the box and not only based on what they have learned from FlipGrid online. That means the research implies a need for a more innovative instructional design for language learning to improve better students’ memorization to learn Mandarin.